Improving Reading Skill through Game Technique for the First Grade Elementary School Students - Silvia Hutabarat; Marwa Yasmine Zaidi (JELITA, 2021)
The present research is a classroom action carried out with procedures starting from planning, action, observation, and reflection. The aim of the study is to obtain a concrete description of the use of game technique in improving students’ reading comprehension skill and the change of students’ behavior during and after learning activities. This research was conducted at SD Islamiyah Medan, involving 35 students as participants. The data was analyzed in three stages, namely: (1) reducing data, (2) presenting data, dan (3) Drawing the conclusion or verifying data. Pre-test and post-test in cycle I showed a very significant increase in reading interest in what was carried out on students with the average score of students. Based on this finding, the playing technique can be used as an alternative by teachers in learning because it is proven that this technique can improve reading comprehension skills which are marked by changes in student behavior.